Language and Philosophy: An Analysis of The Relationship, Weaknesses, and Role of Analytic Philosophy in Epistemology - Budi, Imanuel Setyo; Wismadewi, I Gusti Agung Galuh (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2025)
This article discusses the complex relationship between language and philosophy, focusing on the weaknesses of language and the role of analytic philosophy in epistemology. The main problems raised include the ambiguity of language, its limitations in conveying abstract concepts, and its impact on philosophical thought. This research uses a qualitative method through content analysis and literature studies of the works of philosophers such as Wittgenstein, Russell, and Gettier, as well as a hermeneutic approach to interpreting texts contextually. It aims to examine how language affects philosophical understanding and how analytic philosophy seeks to address the weaknesses of language through logical and semantic analysis. The results show that language, although vital in communication and the construction of reality has limitations such as ambiguity and dependence on context. Analytic philosophy plays a role in clarifying meaning, analyzing concepts, and overcoming misunderstandings through an epistemological approach. This article suggests the need for further research on language in the context of digital technologies and the integration of language philosophy into the educational curriculum to enrich cross-disciplinary understanding. Implicitly, collaborations with cognitive sciences and sociology can provide new insights into the dynamics of language and thought.